(untitled) (LACCEI, 2024)
Thermal comfort is one of the essential elements to improve the comfort and satisfaction of hotel guests. In Andagua, a Peruvian high Andean town where temperatures can drop below 0°C, buildings do not provide adequate thermal comfort for occupants to feel comfortable inside the building, which impacts the length of stay and the profitability of the hotel business. This study evaluates the commercial insulation materials available in Andean cities through software simulations to determine which provides the best insulation to improve the thermal comfort of hotel rooms. The results indicate that thermal insulating materials accompanied by a heating system can change the cold thermal sensation to slightly cool throughout the day. According to the Fanger method, only 20% of the guests will feel discomfort in these conditions, thus improving their satisfaction and increasing the length of their visit to the hotel.